Over Growth: a metabolic densification of Cape Town - Saczek, Ted (School of Architecture, Planning and Geomatics, 2017)
Contemporary cities are experiencing unprecedented growth to cater for growing populations and immigration into urban centres. As a result cities are becoming increasingly densified especially in developing countries2. Densification, and the associated growth, provides many social and cultural benefits, but can lead to increased pollution, environmental degradation, the destruction of existing urban fabric, a lack of greenery, a lack of light to street level, unmanageably large, decaying buildings and increased pressures on infrastructure. This dissertation argues that the design of densified spaces is of utmost importance if we are to maintain a healthy operating space for humanity and the planet. Since before the industrial revolution our society has become governed by a mechanistic way of thinking that originates from technology and science. These thought patterns have shaped the way we design and perceive architecture globally. Many other aspects of society are also influenced by the same mechanistic thought, including our global economic system. This system focuses on indefinite growth; a goal that our finite planet cannot sustain. This paradigm suggests that new, complex approaches to city growth need to be considered to avoid impending disasters. Over Growth investigates various biological concepts that can be applied to densification. Metabolism is used to understand how Cape Town can become more socially and ecologically sound. It suggests that to retain its local character and multi-cultural identity new buildings should grow over valuable, existing urban fabric. The cell is used to interrogate basic increments of city growth. These range from from the scale of an urban block, to individual ERF sizes and to the basic units of the proposed architecture. Symbiosis suggests that cities can exist in harmony with the natural environment. City growth, as an organic process, facilitates the necessary shift away from rational, dualistic thinking towards more complex solutions. These ideas are applied to the South African context, and in particular, a site on Bree Street. Many cities in the developing world continue to aspire to the western models of development. The development of Cape Town is thus threatened by the predominant mechanistic worldview. Conversations with Gawie Fagan, an architect and occupant of the chosen site, gave insight into the city's future and its past, explained later. In general this process was open, collaborative and interdisciplinary to be congruent with the push towards complexity over mechanistic thinking. In short, I develop an approach to architecture that could most suitably alleviate the negative affects of densification in central Cape Town. These include: the deconstruction of spatial hierarchies by using the idea of cellularity to create a more diverse, inclusive social realm; the adaptation, configuration and tectonic of cells; the provision of structure, services and greening to accommodate future additions in a layered 'over growth' that is simultaneously occupied and under construction; and the malleability of the city's zoning regulations and its densification strategy.